Effect of glass fibre reinforced polymer composite material on structural performance of reinforced concrete beams through experimental observation and finite element modelling : A critical review - Solahuddin, Azuwa; Fadzil, Mat Yahaya (Institution of Structural Engineers, 2025)
As a composite material, glass fibre reinforced polymer (GFRP) has several uses. Incorporating CFRP composite material has enhanced the structural behaviour of reinforced concrete beams (RCB) as external reinforcement. It is also important to compile a summary of how different RCB characteristics are affected by GFRP. This review paper discusses the use of GFRP to reinforce RCB and presents a brief description of the topic. Previous experimental investigation and finite element analysis results showed that RCB constructed with GFRP significantly improved the flexure, stiffness, young modulus, load-deflection, ultimate load capacity, load-axial, fracture pattern, stress-strain distribution, and failure mechanism of RCB. Since this GFRP composite material has superior strength, force, load, corrosion resistance, adhesive, and anchoring properties, it can be used as an external reinforcement for RCB. The structural behaviour and performance of RCB can be enhanced by utilising GFRP composite material in civil and structural engineering, especially during building construction.